Environmental crisis and information crisis: reflections on public opinion in the context of sustainability - Galleli, Giovanna Migotto da Fonseca; Leitzke, Milene Rocha Lourenço (Organicom, 2016)
The purpose of this essay is to promote reflections on the behavior of public opinion concerning the environmental crisis, which is at the heart of the sustainability debate. It is based on the premise that there is an information crisis in the environmental crisis, revealing, on the one hand, a vision of sustainability as a market strategy, based on sustainable discourses for profit and image gain, and, on the other hand, distrust over the real dimension of the risks involving the exploitation of natural resources. After reviewing the literature, one comes at the understanding that the context of sustainability is permeated by “non-attitudes”, artificial, unstable and empty-of-content opinions.